The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5694/mja14.00471
|View full text |Cite
|
Sign up to set email alerts
|

Medical tourism raises questions that highlight the need for care and caution

Abstract: The opinions expressed and arguments employed here are the responsibility of the author(s) and do not necessarily reflect those of the OECD. 2 SUMMARY 1.The global growth in the flow of patients and health professionals as well as medical technology, capital funding and regulatory regimes across national borders has given rise to new patterns of consumption and production of healthcare services over recent decades. A significant new element of a growing trade in healthcare has involved the movement of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Healing times were otherwise poorly reported or not mentioned by the majority of authors. Eight authors reported neovagina cavity depth of at least 13 cm (Table 2), achieving an additional 5 cm and good patient satisfaction 19,22,27,29 . Neovagina width was widely under reported.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Healing times were otherwise poorly reported or not mentioned by the majority of authors. Eight authors reported neovagina cavity depth of at least 13 cm (Table 2), achieving an additional 5 cm and good patient satisfaction 19,22,27,29 . Neovagina width was widely under reported.…”
Section: Resultsmentioning
confidence: 97%
“…Eight authors reported neovagina cavity depth of at least 13 cm (Table 2), achieving an additional 5 cm and good patient satisfaction. 19,22,27,29 Neovagina width was widely under reported. Neocavity dimensions reported ranged from intraoperative measurements to measurements taken at last follow up at 11.9 months.…”
Section: Resultsmentioning
confidence: 99%
“…The patient's privacy and confidentiality are important. Furthermore, tourists must be informed about how to prepare themselves for potential endemic diseases at the destination area such as pre-visit vaccination, possible traveler's disease, and climate conditions [21]. In summary, the success factors for medical tourism are multidisciplinary collaboration, simplicity and accessible services, which include the availability of sufficient amount of information via global marketing.…”
Section: Medical Tourismmentioning
confidence: 99%
“…The article by Greenfield and Pawsey highlights the risks associated with medical tourism which is increasingly common among Australians 1 . Cosmetic procedures like tattooing also place people at high risk of acquiring such infections.…”
mentioning
confidence: 99%